Analisis Beban Mental Pekerja untuk Perbaikan Sistem Kerja pada Konveksi XYZ dengan Metode NASA-TLX - Gisya Amanda Yudhistira; Melinska Ayu Febrianti; Mohammad Arsyad Fathurrohman (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2020)
The human resources for companies engaged in production are very important. One of the production companies that continues to experience increased demand is XYZ Convection Yogyakarta. Many demands have an impact on worker conditions, especially with regard to mental workload. This can lead to a decrease in productivity at a time. The study aims to provide an evaluation of workers mental workload based on experimental calculations in experiments. In this study, subjective measurements were made with nasa-TLX method against tailors. There are six indicators to be compared and rated. Calculations from the study showed that the average employee mental workload was 54.08 and was in the high category. Then, analyze the factors that cause high mental load using fishbone diagrams and obtain several affecting factors such as lack of rest time, high demand, number of workers, maintenance of machinery, and environmental circumstances. This indicates that the high workload at XYZ convection is higher than the capacity of its workers.